Profiles of stroke regulations discriminate between finishing positions during international open water races - Bouvet, A.; Pla, R.; Delhaye, E.; Nicolas, G.; Bideau, N. (Journal of Sports Sciences, 2023)
This study aims to identify stroke regulation profiles and tipping-points in stroke regulation timing during international open water races according to performance level. Twelve elite or world-class swimmers were analysed during 18 international races. Stroke rate and jerk cost were computed cycle-to-cycle using an Inertial Measurement Unit and regulations profiles fitted using polynomials. We performed two-ways mixed-ANOVA to compare stroke kinematics among race segments and performance groups (G1 -fastest- to G3 -slowest-). Swimmers displayed specific regulation profiles (i.e., J-shape with end-spurt, J-shape without end-spurt and reverse L-shape for stroke rate and U-shape, reverse J-shape and reverse L-shape for jerk cost, for respectively G1, G2 and G3) with significant effect of race segment on stroke kinematics for G1 and G2. We highlighted tipping-points in stroke regulations profiles (TP1 and TP2) at respectively 30% and 75% of the race with greater magnitude in G1 than G2. TP1 reflects the end of a stroke economy period (0-30%) and TP2 the end of a progressive increase in stroke kinematics (30-75%) towards end-spurt (75-100%). Open water races follow a high-grading dynamics requiring biomechanical regulations along the race. Targeting stroke rate reserve and management of stroke smoothness should be considered during training of open water swimmers.